The Effect of N-linked Glycosylation on Molecular Weight, Thrombin Cleavage, and Functional Activity of Human Protein S - Lu, Deshun; Xie, Rong-Lin; Rydzewski, Andrzej; Long, George L (Thrombosis and Haemostasis, 1997)
Human protein S (HPS) has three potential N-linked glycosylation sites at Asn458’468’489. To study the role of glycosylation at these sites, PCR mutagenesis was used to abolish the consensus sequence of each N-linked glycosylation site (Asn458→Gln, Ser460→Gly; Asn468→Gln, Thr470→Gly; Asn489→Gln, Thr491→Gly) in full-length HPS cDNA. Each resulting construct was expressed in human kidney 293 cells by stable transfection of cDNA/SV40/adeno/pBR322-derived expression vectors, and conditioned medium was collected for recombinant protein purification. SDS-PAGE gels revealed that glycosylation mutants migrate identically and faster than the wild-type rHPS, showing that each of the three potential N-glycosylation sites contain a similar amount of carbohydrate. Mass spectral analysis yielded similar results and a molecular mass of ~78,000 for wild-type HPS. To demonstrate that the difference in mobility between wild-type and mutant protein S is due to their carbohydrate content, plasma-derived HPS and recombinant HPS were subjected to N-glycanase digestion and subsequently shown to migrate identically on SDS-PAGE gels. All forms of HPS have similar time courses for cleavage by α-thrombin. Functional studies indicate that wild-type rHPS possesses the same cofactor specific activity as plasma-derived HPS, as tested by a standard clotting assay. Asn458 and Ser460 mutant rHPS have only a slightly higher cofactor activity, whereas the other four mutants have similar clotting activities, compared to wild-type rHPS. In a purified component system, glycosylation mutants of protein S showed a slightly enhanced ability to stimulate APC-mediated factor Va inactivation after an initial lag phase. The interaction of rHPS glycosylation mutants with human C4b-binding protein (C4bp) was also studied by solution phase equilibrium binding assay. Two mutants (Asn458, Ser460) have marginally lower dissociated constants (Kd) with C4bp, whereas the others have the same apparent Kd as wild-type rHPS.